2017
DOI: 10.1007/s13593-017-0457-3
|View full text |Cite
|
Sign up to set email alerts
|

Diverse concepts of breeding for nitrogen use efficiency. A review

Abstract: Cropping systems require careful nitrogen (N) management to increase the sustainability of agricultural production. One important route towards enhanced sustainability is to increase nitrogen use efficiency. Improving nitrogen use efficiency encompasses increasing N uptake, N utilization efficiency, and N harvest index, each involving many crop physiological mechanisms and agronomic traits. Here, we review recent developments in cultural practices, cultivar choice, and breeding regarding nitrogen use efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 125 publications
(222 reference statements)
5
83
0
Order By: Relevance
“…The current study, as well as several others (Cormier et al, 2013;Mahjourimajd et al, 2016), suggested the need for a better definition for NUE due to the criticisms that have been reported for the initial NUE (calculated according to Moll et al, 1982) that focus only on productivity. Moreover, selecting genotypes for NUE using Moll's model could be misleading because it does not consider genotype efficiency under low N supply and response under high N supply (Lammerts van Bueren and Struik, 2017). Therefore, achieving the maximum NUE will be attained at the lowest N supply used, which will most likely be at the expense of productivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study, as well as several others (Cormier et al, 2013;Mahjourimajd et al, 2016), suggested the need for a better definition for NUE due to the criticisms that have been reported for the initial NUE (calculated according to Moll et al, 1982) that focus only on productivity. Moreover, selecting genotypes for NUE using Moll's model could be misleading because it does not consider genotype efficiency under low N supply and response under high N supply (Lammerts van Bueren and Struik, 2017). Therefore, achieving the maximum NUE will be attained at the lowest N supply used, which will most likely be at the expense of productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, achieving the maximum NUE will be attained at the lowest N supply used, which will most likely be at the expense of productivity. Moreover, selecting genotypes for NUE using Moll's model could be misleading because it does not consider genotype efficiency under low N supply and response under high N supply (Lammerts van Bueren and Struik, 2017). Also, NUE allocates most of the GY to the soil available N (which is difficult to estimate, especially as roots often grow deeper than the soil tested), and it does not consider any other N sources (i.e., mineralization of the organic matter, atmospheric N deposition, N in irrigation and rainwater; Cormier et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a trait-based approach has been recommended for the study of plant-soil interactions and plant legacy effects (Bardgett, Mommer & De Vries 2014;Kardol et al 2015;Bardgett 2017), as well as agro-ecosystem functioning to inform sustainable management practices (Martin & Isaac 2015;Wood et al 2015;Lammerts van Bueren & Struik 2017). …”
Section: Plant Functional Trait Ecologymentioning
confidence: 99%
“…Moreover, in agro-ecosystems there is ample scope to also study impacts of intra-specific trait variation and plant legacy effects as well (Philippot et al 2013;Milla et al 2015;Lammerts van Bueren & Struik 2017). For example, Brassica crop and cultivars vary in levels of secondary metabolites and their ability to suppress plant parasitic nematodes (Fourie et al 2016;Park et al 2017).…”
Section: Lessons From Agricultural and Natural Ecosystemsmentioning
confidence: 99%